Analisis Analysis of Internal and External Factors Affecting the Share Price of Food and Beverage Sector Companies Listed on the Indonesia Stock Exchange (BEI) for the Period 2018-2023 - Abyaan Basyaar Roofif; Ety Dwi Susanti (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to determine the analysis of the effect of Return on Equity (ROE), Earning per Share (EPS), Inflation, and Interest Rates on the Share Price of food and beverage sector companies listed on the Indonesia Stock Exchange during the period 2018-2023. This research is quantitative research using secondary data taken from data published through the Indonesia Stock Exchange and Bank Indonesia websites. The population of all food and beverage companies listed on the Indonesia Stock Exchange for the period 2018-2023 with a total of 34 companies and sampled using the documentation method on an annual scale so that 78 samples were determined. The data analysis technique in this study used multiple linear regression analysis methods. The results found are Return on Equity (ROE) and Earning per Share (EPS) contribute to Stock Prices, while Inflation and Interest Rates do not contribute to Stock Prices.